Six Sigma FMEA Roadmap for Beach Chair Defect Reduction: Roadmap Six Sigma FMEA untuk Pengurangan Cacat Kursi Pantai - M. Frizky Feri Setiawan; Enny Aryanny (Academia Open, 2026)
General Background: Product quality control is a critical factor in export-oriented furniture manufacturing, where defect reduction and process capability are central to sustaining competitiveness. Specific Background: PT XYZ, a wood furniture manufacturer producing beach chair model X for export, recorded an average defect rate of 8.65% during January–December 2025, with five Critical to Quality (CTQ) categories: cracked wood, uneven paint, loose weaving, loose fabric, and unattached nuts. Knowledge Gap: Although Six Sigma and Failure Mode and Effects Analysis (FMEA) are widely applied in manufacturing, their integrated application for systematic defect mapping and risk prioritization in beach chair production at PT XYZ had not been formally analyzed. Aims: This study aims to measure process capability, identify root causes of defects, and formulate prioritized improvement proposals using the DMAIC framework and FMEA. Results: From 3,007 units produced, 171 defective units were identified, yielding an average DPMO of 17,291 and a sigma level of 3.66. P-chart analysis revealed several out-of-control points, indicating special cause variation. FMEA evaluation showed the highest Risk Priority Number (RPN) of 343 for the failure mode “product proceeds without nut verification,” followed by undetected initial wood cracks (RPN 336) and uneven paint layers (RPN 252). Novelty: This study presents an integrated Six Sigma–FMEA roadmap that links statistical process control, root cause analysis, and structured risk prioritization in beach chair manufacturing. Implications: The proposed recommendations provide a data-driven reference for systematic quality control and support the company’s zero defect target in export furniture production. Highlights: Process capability averaged 3.66 sigma with 17,291 DPMO across 3,007 units. The most critical failure mode reached an RPN value of 343 in assembly operations. Statistical control charts identified multiple special-cause variations requiring corrective action. Keywords:Six Sigma, FMEA, DMAIC, Defect Reduction, Risk Priority Number